Analysis of The Effect Earnings Management, Financial Ratios, Governance On Bond - Hartono; Krisdiana; Cuk Jaka Purwanggono; Samuel PD Anantadjaya; Teguh Setiawan Wibowo (PT Mattawang Mediatama Solution, 2022)
The purpose of this study is to analyze the concentration on board profit factors, the proportion of liquidity, administrative ownership and review quality used to anticipate organizational security ratings. This study intends to provide experimental evidence that board income, monetary proportion and corporate administrative mechanisms affect security ratings. The subject of this exploration is an organization listed on the IDX and registered in Indonesia, PT. PEFINDO 2016-2019. Information check using strategic relapse investigation. The results showed that executive earnings, the proportion of liquidity, administrative ownership and review quality had an effect on bond ratings. While action proportion, market price proportion, institutional ownership and free head have no impact on security evaluation.